Environmental efficiency of olive oil production by small and micro-scale farmers in northern Jordan: Life cycle assessment. (October 2016) - El Hanandeh, Ali; Gharaibeh, Mamoun A.
Abstract: Olive groves cover nearly 73% of the total tree-planted agricultural land in Jordan, making olive oil production one of the most important agri-business sectors in the country. Nearly half of the olive trees are planted in the northern region of Jordan where the sector is dominated by small and micro-scale farming practices. Olive farmers rely on traditional production methods with little mechanization or chemicals use. To better understand the environmental impact of the industry on the environment and to compare it to other olive oil production practices in the Mediterranean region; life cycle assessment study was carried out. Five environmental impact categories relevant in the context of Jordan were assessed: acidification (AP); particulate matter formation (PM10 ); human toxicity (HTP); climate change (GWP100 ) and agricultural land occupation (AGLO). The study revealed that olive oil production in the northern region of Jordan is environmentally efficient when compared to large scale production practices common in other Mediterranean olive oil producing countries. On average, the production of 1 kg of olive oil in northern Jordan contributed: 0.57 kg CO2eq to GWP100 ; 11.8 × 10 − 3 kg SO2eq to AP; 5.99 × 10 − 3 kg PM1 0eq ; 0.77 kg 1, 4-DBeq to HTP and 22.54 m 2 ∗ a to AGLO. Uncertainty due to variation at farm level practices affected all impact categories. Monte Carlo analysis showed that GWP100 was the most sensitive to variation at farm level practices while HTP was the least sensitive. Nevertheless, despite the high level of uncertainty, Monte Carlo analysis suggested that the GWP100 was < 1.55 kg CO2eq, 95% of the time. The efficiency of the Jordanian small and micro-olive oil production sector is due to its low level of water, energy and chemical usage in the agriculture phase and the efficient use of waste material for energy production to displace fossil fuel. Soil management practices are the major contributor of the environmental impacts. The system may be further improved if farmers adopt low tillage or no-tillage practices. Graphical abstract: Highlights: Olive oil production in northern Jordan was analyzed using LCA. Small and micro-scale dry organic farming practices are dominant. The sector is environmentally efficient. Soil management is the main contributor to environmental impacts. Low mechanization and solid waste use as fuel is key to lowering the impacts.